2020
DOI: 10.1108/ijem-11-2019-0393
|View full text |Cite
|
Sign up to set email alerts
|

How do teaching quality and pedagogical practice enhance vocational student engagement? A mixed-method classroom observation approach

Abstract: PurposeThe purpose of this paper is to investigate vocational teaching behaviours in facilitating pedagogical practice concerning students' classroom engagement.Design/methodology/approachA mixed-method approach with quantitative classroom observations and qualitative field notes was conducted at two higher vocational institutions in Guangdong province, south of China. Sixty lesson observations were rated combining with supplementary field notes from 20 teacher participants analysed through a comparative codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…During the classroom observation, the researcher took the advice from scholars [53,76] to adopt both a wide and narrow perspectives to examine how the English teachers' teaching goals were attained. While adopting a wide perspective, the researcher focussed on the overall situation, whereby the lesson design, teaching quality, the richness of teaching contents, student engagement in activities, teacher-student relationship and the relationship between the teacher and student behaviours alongside the physical environment were scrutinised [76][77][78]. While adopting a narrow perspective, the researcher focussed on a single person or activity.…”
Section: Classroom Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the classroom observation, the researcher took the advice from scholars [53,76] to adopt both a wide and narrow perspectives to examine how the English teachers' teaching goals were attained. While adopting a wide perspective, the researcher focussed on the overall situation, whereby the lesson design, teaching quality, the richness of teaching contents, student engagement in activities, teacher-student relationship and the relationship between the teacher and student behaviours alongside the physical environment were scrutinised [76][77][78]. While adopting a narrow perspective, the researcher focussed on a single person or activity.…”
Section: Classroom Observationmentioning
confidence: 99%
“…For instance, while the researcher was focussing on the teachers, their enthusiasm for engaging their students in meaningful activities, clarity in delivery and body gestures were carefully watched. While focussing on students, the researcher paid attention to whether they understood the relevant concepts, acquired the relevant skills such as reading, speaking, critical thinking, expressed their thoughts clearly in an organised manner and reflected their learning [76][77][78]. Field notes were taken during the classroom observations, whereby the researcher noted down the physical maps of the settings, keywords of the teacherstudent and student-student conversations and other relevant background information to describe the behaviours of teachers and students during the classroom observations so as to gain additional evidence of students' responses and their learning outcomes [68,75,76].…”
Section: Classroom Observationmentioning
confidence: 99%
“…The study provides nascent theoretical insights to the limited research on perceived value for AE in higher education online learning context. Higher education policymakers are better informed of the proactive steps to increase any possible positive effects of perceived value (Zhao and Ko, 2020). Still, since TB did not fully mediate the perceived value–engagement association as underpinned by the social motivational theory, it can be inferred that the anticipated relatedness is not facilitated yet fully by teachers and so a long-term observation of the model variables is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that students who have had negative past experiences with education appreciate and rely on a structured academic experience to fully engage with their learning (Hellmundt & Baker, 2017). Furthermore, previous research indicated that clear instructions are strongly related to increased student engagement (Ko et al, 2017;Maulana & Helms-Lorenz, 2017;Zhao & Ko, 2020). This was consistent with the findings of this study, as all participants reported that the well-organized structure of their program was a necessary aspect in their reintroduction to an education setting.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%